2017
DOI: 10.1016/j.kint.2017.01.009
|View full text |Cite
|
Sign up to set email alerts
|

The leukotriene B4–leukotriene B4 receptor axis promotes cisplatin-induced acute kidney injury by modulating neutrophil recruitment

Abstract: Cisplatin is an effective chemotherapeutic agent and widely used in treatment of various solid organ malignancies, including head and neck, ovarian, and testicular cancers. However, the induction of acute kidney injury (AKI) is one of its main side effects. Leukotriene B receptor 1 (BLT1) mediates the majority of physiological effects of leukotriene B (LTB), a potent lipid chemoattractant generated at inflammation sites, but the role of the LTB-BLT1 axis in cisplatin-induced AKI remains unknown. Here we found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 44 publications
1
39
0
Order By: Relevance
“…However, discordant results led to questioning of the role of neutrophils during early AKI pathogenesis [2]. Recent studies, however, have shown that blocking neutrophil infiltration by inhibition of vascular adhesion protein-1 or leukotriene B4-leukotriene B4 receptor axis had protective effect against ischemia-reperfusion injury (IRI) and cisplatin-induced AKI, respectively [3,4]. …”
Section: Immune Cells In Akimentioning
confidence: 99%
“…However, discordant results led to questioning of the role of neutrophils during early AKI pathogenesis [2]. Recent studies, however, have shown that blocking neutrophil infiltration by inhibition of vascular adhesion protein-1 or leukotriene B4-leukotriene B4 receptor axis had protective effect against ischemia-reperfusion injury (IRI) and cisplatin-induced AKI, respectively [3,4]. …”
Section: Immune Cells In Akimentioning
confidence: 99%
“…In one study, cisplatin induced the biosynthesis of LTB 4 and the expression of its BLT1 receptor in the kidney. The BLT1 receptor antagonist U-75302, BLT1 deficiency and the LTA 4 H inhibitor SC-57461A reduced kidney structural and functional damage, inflammation and apoptosis [ 23 ]. It should be noticed, however, that inhibition of LTA 4 H might direct its substrate LTA 4 towards increased biosynthesis of cysteinyl leukotrienes.…”
Section: Leukotrienes As Mediators Of Drug-associated Nephrotoxicitymentioning
confidence: 99%
“…[3] LTB4 IN KIDNEY INJURY [4] 1) Leukotriene B4 receptor 1 (BLT1) mediates the majority of physiological effects of leukotriene B4 (LTB4), a powerful lipid chemo-attractant produced at inflammation sites, but the role of the LTB4-BLT1 pathway in cisplatin-induced AKI remains unknown. [4] 2) Up-regulated LTB4 production and BLT1 expression in the kidney after cisplatin administration. Cisplatin was found to directly up-regulate gene expression of leukotriene A4 hydrolase and stimulate LTB4 production in renal tubular epithelial cells.…”
Section: Diabetes and Leukotrienesmentioning
confidence: 99%
“…Reduced kidney structural/functional damage, inflammation, and apoptosis. [4] 3) LTB4-BLT1 pathway contributes to cisplatin-induced AKI by mediating kidney recruitment of neutrophils, which bring inflammation and apoptosis in the kidney.…”
Section: Diabetes and Leukotrienesmentioning
confidence: 99%
See 1 more Smart Citation